Precision fertigation: The key component for maximizing productivity - Lingavale, Tejas Mangesh; Jadhav, H T; Pawar, D P (Indian Farming, 2023)
Fertigation plays a very crucial role in enhancing plant productivity. Presently, fertigation is done by various devices available in the market. They are having certain limitations and lower fertilizer use efficiency due to the non-uniform mixing of water-soluble fertilizers, uneven injection rate, non-uniform distribution of fertilizer throughout the entire field, etc. Considering the costs and drawbacks of the available fertigation systems, it was felt necessary to develop a cost-effective, userfriendly and efficient fertigation system that would be made easily from materials available in the market. Accordingly, a three-stage fertigation system was developed that can decide appropriate fertilizers quantity, mix them well and distribute them evenly throughout the field with significant uniformity. This article’s goal is to give readers a concise overview of the three-stage fertigation system along with its benefits over the existing fertigation systems, the procedure to give fertigation by the developed system, general guidelines to be followed while giving fertigation using the developed system and potential for automation in the future to bring the more accuracy in the fertigation.